THE USE OF SHOPEE LIVE AS AN ALTERNATIVE BUSINESS OPPORTUNITY FOR MSME EMPLOYEES OF MITRA NEW HASELLA CONVECTION - S.Pd. M.Si, Tutik (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
New Hasella is a type of MSME engaged in home convection, where New Hasella itself has become one of the largest convections in Pakalongan Regency with distribution spread across the cities of Solo, Yogyakarta and Surabaya. New Hasella Convection has partners from local residents who collaborate in the production process in the sewing section. However, with the limited income they have, partners must look for alternative businesses to be able to increase their income, namely by utilizing Shopee live as a promotional and sales medium. The results of this study are that the use of Shopee live is an effective and efficient alternative business opportunity because in addition to partners being able to connect with consumers at large, partners also get additional income. In addition, with this business, not only partners benefit, but New Hasella also feels an increase in income. So that mutual prosperity is achieved between New Hasella and partners. This research is a field research with a qualitative descriptive approach. The data source that the researcher conducted in this study is using primary data with a data collection method using Focus Group Discussion (FGD).